Establishment of Kinetic Model for Catalytic Pyrolysis of Daqing Atmospheric Residue - 刘熠斌 陈小博 赵辉 杨朝合 (Chinese journal of chemical engineering, 2009)
An 8-lump kinetic model was proposed to predict the yields of propylene, ethylene and gasoline in the catalytic pyrolysis process of Daqing atmospheric residue. The model contains 21 kinetic parameters and one for catalyst deactivation. A series of experiments were carded out in a riser reactor over catalyst named LTB-2. The ki- netic parameters were estimated by using sub-model method, and apparent activation energies were calculated according to the Arrhenius equation： The predicted yields coincided well with the experimental values. It shows that the kinetic parameters estimated by using the sub-model method were reliable.